A Roadmap to Integrating Dermatologic Care at a Student-Run Free Health Clinic - Yacine Sow; Loren Krueger; Christopher Ervin; Maher Alharthi; Ronnie Festok; Moses Elam; Danielle Duvernay; Folashade Omole (Journal of Student-Run Clinics, 2024)
Student-run free health clinics (SRFCs) play an important role in providing a safety net healthcare system for uninsured patients by offering primary healthcare or preventative medical services. Patients at free clinics may have to be referred out for medical complaints better managed with specialty care. Integrating these services at SRFCs can address barriers to accessing specialty care. Free dermatologic care offers an opportunity to provide care to patients who may otherwise ignore symptoms, which can lead to reduced quality of life and a worse prognosis in some conditions. We detail a roadmap to integrate dermatologic services at an SRFC by providing operational considerations such as assessing needs, developing a clinical workflow, engaging dermatologists and the community, and sustaining student involvement. We also discuss the potential for a dermatology clinic to foster interest in the specialty among students underrepresented in medicine, given the current call to action to increase racial and ethnic diversity in the dermatologic workforce.